SDR Currency Basket-Proposed Extension of the Valuation of the SDR. (Policy Papers; Policy Paper ;, 2015)
This paper proposes an extension of the current SDR valuation basket for a period of nine months to September 30, 2016. This extension would respond to feedback from SDR users on the desirability of avoiding changes in the basket at the end of the calendar year and facilitate the continued smooth functioning of SDR-related operations. As discussed at the informal Board meeting on July 29, this proposal does not in any way prejudge the outcome of the Review of the Method of Valuation of the SDR.